Mapping phenotypic and aetiological associations between ADHD and physical conditions in adulthood in Sweden: a genetically informed register study. (September 2021) - Du Rietz, Ebba; Brikell, Isabell; Butwicka, Agnieszka; Leone, Marica; Chang, Zheng; Cortese, Samuele; D'Onofrio, Brian M; Hartman, Catharina A; Lichtenstein, Paul; Faraone, Stephen V; Kuja-Halkola, Ralf; Larsson, Henrik
Summary: Background: Emerging evidence suggests increased risk of several physical health conditions in people with ADHD. Only a few physical conditions have been thoroughly studied in relation to ADHD, and there is little knowledge on associations in older adults in particular. We aimed to investigate the phenotypic and aetiological associations between ADHD and a wide range of physical health conditions across adulthood. Methods: We did a register study in Sweden and identified full-sibling and maternal half-sibling pairs born between Jan 1, 1932, and Dec 31, 1995, through the Population and Multi-Generation Registers. We excluded individuals who died or emigrated before Jan 1, 2005, and included full-siblings who were not twins and did not have half-siblings. ICD diagnoses were obtained from the National Patient Register. We extracted ICD diagnoses for physical conditions, when participants were aged 18 years or older, from inpatient (recorded 1973–2013) and outpatient (recorded 2001–13) services. Diagnoses were regarded as lifetime presence or absence. Logistic regression models were used to estimate the associations between ADHD (exposure) and 35 physical conditions (outcomes) in individuals and across sibling pairs. Quantitative genetic modelling was used to estimate the extent to which genetic and environmental factors accounted for the associations with ADHD. Findings: 4 789 799 individuals were identified (2 449 146 [51%] men and 2 340 653 [49%] women), who formed 4 288 451 unique sibling pairs (3 819 207 full-sibling pairs and 469 244 maternal half-sibling pairs) and 1 841 303 family clusters (siblings, parents, cousins, spouses). The mean age at end of follow-up was 47 years (range 18–81; mean birth year 1966); ethnicity data were not available. Adults with ADHD had increased risk for most physical conditions (34 [97%] of 35) compared with adults without ADHD; the strongest associations were with nervous system disorders (eg, sleep disorders, epilepsy, dementia; odds ratios [ORs] 1·50–4·62) and respiratory diseases (eg, asthma, chronic obstructive pulmonary disease; ORs 2·42–3·24). Sex-stratified analyses showed similar patterns of results in men and women. Stronger cross-disorder associations were found between full-siblings than between half-siblings for nervous system, respiratory, musculoskeletal, and metabolic diseases (p<0·007). Quantitative genetic modelling showed that these associations were largely explained by shared genetic factors (60–69% of correlations), except for associations with nervous system disorders, which were mainly explained by non-shared environmental factors. Interpretation: This mapping of aetiological sources of cross-disorder overlap can guide future research aiming to identify specific mechanisms contributing to risk of physical conditions in people with ADHD, which could ultimately inform preventive and lifestyle intervention efforts. Our findings highlight the importance of assessing the presence of physical conditions in patients with ADHD. Funding: Swedish Research Council; Swedish Brain Foundation; Swedish Research Council for Health, Working Life, and Welfare; Stockholm County Council; StratNeuro; EU Horizon 2020 research and innovation programme; National Institute of Mental Health.